DISAPPOINTING AND BEING DISAPPOINTED: VIDEO GAME PLAYER TRUST IN EACH OTHER - Tomlinson, Christine (AoIR Selected Papers of Internet Research, 2019)
Hostility in video games has been a cause for concern since multiplayer gaming began gaining popularity. Many of the studies conducted on this topic have highlighted negative behaviors as particularly aggressive toward women, but relatively limited in the broad context of general audiences or in contrast to positive multiplayer encounters . This study uses interviews with 54 people and approximately 1900 online forum posts to further investigate player experiences with and understandings of hostility in video game play. Overall, it appears that female players do experience particular kinds of harassment, but that players have been negatively influenced and affected by these types of behavior regardless of gender. Largely, players have begun to feel like they cannot feel comfortable in these spaces or necessarily trust other players to behave in positive ways. For both male and female players, this has led to many avoiding certain types of game or specific titles all together. Additionally, players lack confidence that companies are doing what is necessary to shift the culture and have come to understand toxic players as something to be expected in the community. Because of its frequency, toxicity has become understood as a part of gaming culture and something that, perhaps, is immutable.